2018
DOI: 10.1242/dmm.035469
|View full text |Cite
|
Sign up to set email alerts
|

Effective CRISPR/Cas9-based nucleotide editing in zebrafish to model human genetic cardiovascular disorders

Abstract: The zebrafish (Danio rerio) has become a popular vertebrate model organism to study organ formation and function due to its optical clarity and rapid embryonic development. The use of genetically modified zebrafish has also allowed identification of new putative therapeutic drugs. So far, most studies have relied on broad overexpression of transgenes harboring patient-derived mutations or loss-of-function mutants, which incompletely model the human disease allele in terms of expression levels or cell-type spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 27 publications
0
67
0
1
Order By: Relevance
“…An important aspect hindering a direct comparison with several previous studies is the different methods used to evaluate the HDR efficiency, such as PCR-or restriction-assays, sequencing of a limited number of clones, genotyping based on high-resolution melting analysis, fluorescence etc. [37][38][39][40]42,44,46 . Only three studies in zebrafish have used NGS, showing lower perfect repair rates of 1-4% 41 , 1.7-3.5% 45 and <1% 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important aspect hindering a direct comparison with several previous studies is the different methods used to evaluate the HDR efficiency, such as PCR-or restriction-assays, sequencing of a limited number of clones, genotyping based on high-resolution melting analysis, fluorescence etc. [37][38][39][40]42,44,46 . Only three studies in zebrafish have used NGS, showing lower perfect repair rates of 1-4% 41 , 1.7-3.5% 45 and <1% 43 .…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of very low efficiency KI of a gene encoding red fluorescent protein in rohu carp 34 , such advanced and fine-tuned genome editing has not been developed for farmed fish, and it may be useful to learn from protocols already established in model fish species. While only a few studies have reported HDR in medaka 35,36 , several KI-strategies have been reported in zebrafish using either donor plasmids [37][38][39] or single-stranded oligodeoxynucleotides (ssODNs) [40][41][42][43][44][45] , or both 46 . Knowledge from other fish studies are somewhat inconclusive when it comes to deciding the strategy for applying HDR in salmon, as there is a lack of consensus regarding the impact of different repair templates, homology arm length and strand complementarity in the above-mentioned studies.…”
mentioning
confidence: 99%
“…Cantu syndrome (CS) is a complex disorder with multiple cardiovascular abnormalities, including edema, dilated and tortuous blood vessels with decreased systemic vascular resistance, patent ductus arteriosus (PDA), and marked cardiac hypertrophy (1). CS is caused by gain-of-function (GoF) mutations in KCNJ8 and ABCC9, which encode pore-forming Kir6.1 and regulatory SUR2 subunits, respectively, of ATP-sensitive potassium (K ATP ) channels (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These subunits are prominently expressed in smooth muscle (SM) cells, and vascular SM (VSM) K ATP channel activation underlies the chronically dilated vasculature observed in patients with CS (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, HDR has been used to generate knockin lines of zebrafish with various efficiencies [12][13][14][24][25][26][27] . For most of reported zebrafish lines generated via HDR, single-stranded oligodeoxynucleotide (ssODN) was usually used as a repair template 14,[24][25][26][27] . This strategy can only achieve genomic alteration with a few of bps such as point mutation and short tag insertion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the requirement for pre-screening cannot be met in many cases. Without pre-screening, genomic editing mediated by HDR in zebrafish shows relatively low efficiencies [25][26][27] , in particular for long DNA fragments 12,14 . This makes it necessary to develop more efficient methods for achieving long DNA fragments replacement.…”
Section: Discussionmentioning
confidence: 99%